“Estado de la regeneración natural del bosque secundario en la hacienda pb54 de la empresa plantabal s.a, cantón la mana, provincia de Cotopaxi” - Cedeño Lizano, Gustavo Andrés (2021)
In this research, the main objective was to evaluate the state of natural regeneration of forest species in the secondary forest of the PB54 farm, owned by PLANTABAL S.A., located in the Poza Honda sector, canton La Maná, Cotopaxi province, a completely randomized design was applied, where 15 plots of 400 m2 were established, an inventory of trees with DBH ≤ 7,5 cm was carried out, recording the common name, characteristics and height of the species. The diversity richness of the forest was evaluated in 3 categories: low grassland, high grassland and saplings. A total of 658 individuals belonging to 20 families, 30 genera and 34 species were found, being the most important families by number of species Rubiacea with 5 species, Melastomataceae and Sapindaceae with 4, Moraceae with 3, followed by Fabaceae and Solanaceae with 2. The Importance Value Index (IVI) indicated that the most ecologically important species in low grassland were Witheringia solanaceae (cojojo) with 16.26%, followed by Piper aduncum (matico) in high grassland with 35.67% and brinzal with Piper aduncum (matico) with 27.20% and the least representative species were: in low grassland, the species Inga sp (guaba de monte) with 4.22%, Miconia sp. (unknown 2) with 1.98% in tall grassland and Castilla elastica (rubber) with 0.60% in saplings. In the diameter distribution, the largest number of individuals, 122, were concentrated in diameter class I of the tall grassland and 158 in class III. Regarding the altimetric classes, the highest number of individuals was found in the low grassland with 93 individuals, followed by the high grassland with 307 and brinzales with 91, the three categories were concentrated in class I. Key words: Natural regeneration, richness, species, IVI and sampling units.